Monitoring projects-it's more than reading reports - Gaynor, Gerard H.
Gerard H. Gaynor describes the proactive role that successful project managers take.
Effective monitoring involves people, the work itself, the project reviews, and-on rare (hopefully) occasions-termination.
Keywords: Projects; Monitoring